A framework of Climate Disaster Resilience Index (CDRI) for environmental components in Kukup-Tanjung Piai, Johor - Asmawi, M. Zainora; Ibrahim, Illyani; Zainal, Megat Sahrir; Abidin, Suriani; A. Razak, Khamarrul; Wan Mohd Rani, Wan Nurul Mardiah (Malaysia Remote Sensing Agency, 2018)
Over the time, Malaysia has been experienced environmental related disasters in relation to the impact of climate change and its associated phenomena. Disasters such as monsoon flood, erosion and landslide are amongst the most common ones hit Malaysia. In this regards, Malaysia highly emphasises the need for having an appropriate management system for disaster risk strategies in its 11th Malaysia Plan (2016-2020), which is parallel with the aspiration of Sendai Framework for Disaster Risk Reduction (2015-2030). The issue of coastal erosion concerning sea level rise has merged significantly in Kukup-Tanjung Piai, Johor. Hence, this research was initiated to develop a framework of the Climate Disaster Resilience Index (CDRI) for environmental components, reflecting the importance of environmental dimensions within the context of land use planning. The analysis is based on a comprehensive review of the literature and used the international directive in developing the proposed framework. This paper presents the GIS-based process in developing a framework of CDRI for environmental components. There are five geographical settings namely built-up areas, forest reserve, erosion, coastal areas, and rivers applied as GIS database for generating the spatial risks areas of coastal erosion. The result for CDRI was obtained via conducting a Focus Group Discussion (FGD) session with 22 participants of various government technical officials. The findings of CDRI indicate that the average score of resilience is relatively moderate with a score of 3.52. The frequency of hazard records the highest score at 3.87 and ecosystem has the lowest score of 3.20. These findings are of particular importance to Pontian District Council and other technical agencies to strengthen their ability and capacity as responding to the risk of coastal erosion in Kukup-Tanjong Piai.